How to Develop Character Education of Madrassa Students in Indonesia - Lukman Abu; Mahani Mokhtar; Zainudin Hassan; Siti Zakiah Darmanita Suhan (Journal of Education and Learning (EduLearn), 2015)
In the last decades, the  teachers criticized for failing to integrate the knowledge in the behavior of virtue. Therefore the character education is always considered in every design education, including in madrassas. The character education is the deliberate attempt to influence the behavior of students through customizing repeatedly. making it easy to do virtue and avoid crime. The research has focused on the approach to character education at madrassa. The qualitative method by interviewing, observation, and focus groups have been used in this study.A total of 16 teachers at four madrassas in South Sulawesi has been selected through purposive Sampling. The  research suggest: Madrassa teachers have not managed to practice the concept of teaching character. Both conceptually and contextually. The failure of conceptually caused teachers do not embed character values are extracted from the behavior of student’s virtue. While the failure of the contextually is has caused teachers failed in an attempt to develop character values, such as social relationships, honesty, and discipline. In addition, the teachers are not managed to practice courteous and not empowered to detain students of behavior lie.